Pengaruh E-WOM terhadap Keputusan Membeli Tiket Umrah pada Akun @umrohbarengyuk.id - Dava Qaulan Sadida; Riska Tyas Prahesti (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
This study explores the influence of Electronic Word of Mouth (E-WOM) on Umrah ticket purchasing decisions through the Instagram account @umrohbarengyuk.id. In today’s digital era, social media serves as a primary channel in shaping consumer perceptions of services, particularly in religious travel industries like Umrah. E-WOM, consisting of interaction intensity, opinion valence, and content quality, plays a vital role in providing trustworthy information and building consumer confidence. Using a quantitative method involving surveys and simple linear regression analysis, the study finds that digital reviews and testimonials strongly influence prospective pilgrims’ decisions. The @umrohbarengyuk.id account is perceived as providing transparent, responsive, and relevant communication, making it a key reference in users’ information-seeking and service evaluation processes. These findings reinforce E-WOM as a powerful digital marketing communication strategy that not only increases service appeal but also enhances customer trust and purchasing confidence. The study offers practical insights for Umrah service providers in developing personalized, credible digital content and strategies to reach broader audiences effectively.